Eating healthfully on a limited income : a multisystemic approach to the barriers low-income populations face in obtaining adequate nutrition in the U.S. - Postiglione, Maryann (Kansas State University, 2014)
Because of the ever-changing nature of the economy and the food environment, research as recent as 2010 may not be relevant to today’s discussion on food insecurity, food deserts, obesity rates, and nutritional quality in the U.S. population’s diet. Today, people of low socioeconomic status in the U.S. are at risk for overweight, obesity, and chronic illnesses such as type 2 diabetes, hypertension, and certain cancers. In this report, I investigate published research about low-income populations in the U.S. relative to the food environment and describe implications for healthcare professionals implementing interventions with these populations, discussed in the following categories: Dietary Intake Quality and Socioeconomic Status; Food Insecurity; Barriers to Quality Food Access in the U.S. Food Environment; Communities Alleviating Food Insecurity; Food-Related Perceptions, Attitudes, and Behaviors; Homelessness and Food-Related Behaviors; Why Do People Buy What They Buy?; Nutrition Assistance Programs and Policies; Current U.S. Food Costs; and Comparing the Nutritional Value Versus Price of Foods. Although the literature on the subject of low-income diet quality is thorough, much of it needs to be updated with current data on food prices, food environments, and U.S. diet quality. For this purpose, I compiled the most recent data from the National Bureau of Labor & Statistics on food prices to discuss the elevated food prices of healthful foods as opposed to less healthful foods. I also created a one-month menu based on the U.S. Department of Agriculture’s Thrifty Food Plan budget allowance in order to follow a healthful diet in this harsh economic climate utilizing the Dietary Guidelines for Americans 2010 and the Affordable Nutrients Index.
Keywords: Low-income; Nutrition; SNAP; Diet Quality Intake; Menu; Thrifty Food Plan; Health Education (0680); Health Sciences, Education (0350); Public Health (0573)